Rinsing of Saline Water from Road Salt in a Sandy Soil by Infiltrating Rainfall: Experiments, Simulations, and Implications - Higashino, Makoto; Erickson, Andrew J.; Toledo-Cossu, Francesca L.; Beauvais, Scott W.; Stefan, Heinz G. (Water, air, and soil pollution, 2017)
Saline melt water from road salt applications that has percolated into a fine sandy soil in winter is rinsed out of the soil by infiltrating rainwater in the following warmer seasons. This sequence of saturated and unsaturated flow processes associated with saline water transport in a fine sandy soil was studied by simulation and exploratory laboratory experiments. Experiments in soil columns of 300-μm sand revealed that two rinses of pure water, each of one pore volume, were sufficient to reduce the salt concentration by 99% of its original value in the soil column. Simulated time variations of salt concentration in the effluent from the column agreed with experimental results. Based on simulated and experimental results, a sandy soil must become saturated to experience pore water flow in order to efficiently rinse saline snowmelt water. Depending on the saturated hydraulic conductivity and the soil depth, days, weeks, or months of freshwater infiltration in summer are needed to rinse saline melt water from an unsaturated sandy soil after road salt applications in winter. This explains findings of significant salt concentrations in surface and shallow groundwater during summer months, long after road salt application and infiltration has ceased.